PRINSIP DAN TEKNIK MENGAJARKAN KOSAKATA BI KEPADA PEBELAJAR BIPA - Susanto, Gatut (Diksi, 2015)
The extent of vocabulary possessed by learners of BIPA, of Bahasa Indonesia sebagai Penutur Asing, or of the Indonesian language as foreign speakers, has a positive correlation with the extent of their achievement in mastering that language. As part of the effort to keep applying communicative teaching, careful attention needs to be paid to the teaching of vocabulary to learners of BIPA in order that it remains on the communicative lane and the vocabulary learned has enduring retention in their memory so that they could make it function both as a means of communication and as a means of performing their speech acts. The syllabus planned for the vocabulary teaching is a curriculum model determining the direction of the teaching program and describes the objectives to be achieved in each learning activity. The syllabus design enables the teachers to formulate lesson plans that are in line with the teaching objectives to be achieved. The plan of the syllabus should be made integrally in order that the vocabulary teaching could be linked with other components like skill aspects of the target language such as function, context, and grammar as well as its cultural aspects. Keywords: vocabulary, foreign speakers, teaching